Membumikan Pancasila di Kalangan Generasi Z untuk Memperkuat Identitas Bangsa - Wahid, St. Hadijah; Sasmita Indah, Mega; Awaliyah, Resky; Nasaruddin, Muh; Adrianto, Adrianto; Zaini, Muhammad Raihan (LANCAH: Jurnal Inovasi dan Tren, 2025)
It is very important to continue discussing national knowledge in line with national and state life. Here is the value of Pancasila acts as a bridge towards the development of national science. Pancasila as a guide to national life and the ideology of the Indonesian state, it is gradually losing its prestige and being replaced by foreign culture carried by the current of globalization. Pancasila actually consists of values that are formulated and sourced from the values of the Indonesian nation itself, and are in harmony with customs and culture that exist in the lives of Indonesian people. The aim of this research is to help the younger generation understand and recognize the forgotten national identity. The research method used in preparing this article is using qualitative research methods. In this method, the author collects data obtained by studying books, articles and other scientific works. The result of this research is that in developing national insight, many Pancasila values can be applied in social and state life. Therefore, art This will help generations to find national identity and love their own culture.